Cleaning sheet and conveying member having a cleaning function
Patent Information
- Application Number
- CN202210264464.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-04-28
- Filing Date
- 2022-03-17
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-03-17
AI Technical Summary
然而,在真空吸附中会出现吸附误差
[0010] The object of this invention is to provide a cleaning sheet including a cleaning layer, which can be applied to a transport member conveyed within a substrate processing apparatus, and which can effectively suppress adsorption errors when the cleaning layer is adsorbed onto an adsorption stage or the like. Another object of this invention is to provide a transport member with a cleaning function, comprising such a cleaning sheet and a transport member.
Smart Images

Figure CN115247031B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to cleaning sheets and delivery components with cleaning functions. Background Technology
[0002] In various substrate processing equipment, such as manufacturing and inspection equipment for semiconductors, flat panel displays, and printed circuit boards, which are susceptible to damage from foreign objects, the transport device (usually a chuck table, etc.) and the substrate are transported while in physical contact with each other. In this case, when foreign objects adhere to the transport device, subsequent substrates are successively contaminated, thus requiring periodic shutdowns of the equipment for cleaning. As a result, the operating rate of the processing equipment decreases, and a significant amount of time and labor is required for cleaning.
[0003] To address the problems described above, a method has been proposed for removing foreign matter adhering to a conveying device by conveying a plate-shaped member within a substrate processing apparatus (see Japanese Patent Application Publication No. Hei 11-87458). According to this method, it is not necessary to stop the substrate processing apparatus for cleaning, thus solving the problem of reduced operating efficiency of the processing apparatus. However, according to this method, it is not possible to sufficiently remove foreign matter adhering to the conveying device.
[0004] Meanwhile, a method for removing foreign matter attached to a conveying device by conveying a substrate with an adhesive substance fixed in it as a cleaning member in a substrate processing apparatus has been proposed (see Japanese Patent Application Publication No. Hei 10-154686). Compared with the method described in Japanese Patent Application Publication No. Hei 11-87458, this method provides superior foreign matter removal performance.
[0005] However, the method described in Japanese Patent Application Publication No. Hei 10-154686 suffers from the problem of excessive adhesion between the adhesive and the conveying device at their contact points, preventing separation between them. This results in unreliable conveying of the substrate with the adhesive attached, damage to the conveying device, and contamination of the conveying device. Furthermore, when the adhesion between the adhesive and the conveying device becomes too weak, the foreign matter removal capability of the cleaning component decreases, leading to insufficient cleaning effectiveness.
[0006] As a means of solving the various problems mentioned above, the applicant has reported a cleaning sheet including a cleaning layer, which uses a polymer component as the material of the cleaning layer used as a cleaning member, and is applicable to a transport member transported in a substrate processing apparatus (Japanese Patent Application Publication No. 2007-307521 and Japanese Patent Application Publication No. 2010-259970).
[0007] When a polymer component is used as the material for the cleaning layer, the cleaning layer is typically formed as described below.
[0008] A varnish containing a polymer component serving as a cleaning layer is applied to the surface of any suitable substrate (e.g., the mirror surface of a silicon wafer) by spin coating, and then heated or dried as needed to form a layer on the substrate.
[0009] However, when cleaning a conveying device (typically a chuck table, etc.) with a cleaning sheet including the cleaning layer obtained as described above or a conveying member with a cleaning function, vacuum adsorption is usually performed by mounting the cleaning sheet or the conveying member with a cleaning function on the adsorption stage of the conveying device, such that the cleaning layer side of the sheet or the member can face the adsorption stage. However, adsorption errors can occur in vacuum adsorption. Summary of the Invention
[0010] The object of this invention is to provide a cleaning sheet including a cleaning layer, which can be applied to a transport member conveyed within a substrate processing apparatus, and which can effectively suppress adsorption errors when the cleaning layer is adsorbed onto an adsorption stage or the like. Another object of this invention is to provide a transport member with a cleaning function, comprising such a cleaning sheet and a transport member.
[0011] The applicant has investigated the causes of adsorption errors. The applicant has then conducted a detailed study, focusing on the following performance of the means used to vacuum adsorb the cleaning layer side of a cleaning sheet or a conveying member with a cleaning function onto the adsorption stage of the conveying device: the sealing performance between the contact sealing member, such as a sealing strip, provided on the adsorption stage and the cleaning layer. As a result, the applicant has disclosed that adsorption errors occur when a rising portion (crown) is formed in the periphery of the cleaning layer of the cleaning sheet or the conveying member with a cleaning function to allow for vacuum adsorption onto the adsorption stage, and the rising portion has a ridge size equal to or greater than a predetermined size. In view of the foregoing, the applicant has studied a method for suppressing adsorption errors by appropriately adjusting the size of the ridge, and has completed the present invention.
[0012] According to at least one embodiment of the present invention, a cleaning sheet is provided, comprising a cleaning layer, wherein when a direction from an end of the surface toward its center when viewed from a normal direction relative to the surface of the cleaning layer is defined as a center direction; and when an area in the surface with a width of 10 mm from the end toward the center direction is defined as an end region, the relationship between the maximum thickness L in the normal direction of the cleaning layer in the end region and the average thickness T in the normal direction of the cleaning layer in the region of the cleaning layer excluding the end region is LT ≤ 5 μm.
[0013] In at least one embodiment, the portion of the cleaning layer having a thickness greater than the average thickness T by more than 1 μm has a width “d” of less than 4,000 μm in the central direction.
[0014] In at least one embodiment, the cleaning layer comprises at least one selected from the group consisting of: polyimide resins; and polybenzoxazole resins.
[0015] In at least one embodiment, the thickness of the cleaning layer is 1 μm to 100 μm.
[0016] In at least one embodiment, the cleaning sheet further includes a pressure-sensitive adhesive layer.
[0017] In at least one embodiment, the cleaning sheet further includes a support.
[0018] According to at least one embodiment of the present invention, a conveying member with a cleaning function is provided, comprising: a cleaning sheet; and a conveying member. Attached Figure Description
[0019] Figure 1 This is a schematic cross-sectional view illustrating a cleaning sheet according to at least one embodiment of the present invention.
[0020] Figure 2 This is a schematic cross-sectional view illustrating a cleaning sheet according to at least one embodiment of the present invention.
[0021] Figure 3 This is a schematic cross-sectional view illustrating a cleaning sheet according to at least one embodiment of the present invention.
[0022] Figure 4 This is a schematic cross-sectional view illustrating a cleaning sheet according to at least one embodiment of the present invention.
[0023] Figure 5 This is a schematic illustration to show the normal direction, center direction, and end regions of a cleaning sheet according to at least one embodiment of the present invention.
[0024] Figure 6 A schematic cross-sectional view is provided to illustrate the difference (LT) between the maximum thickness L in the normal direction of the cleaning layer in the end region and the average thickness T in the normal direction of the cleaning layer in the regions other than the end region of the cleaning layer in a cleaning sheet according to at least one embodiment of the invention.
[0025] Figure 7 This is a schematic cross-sectional view showing the width in the central direction of a portion of the cleaning layer having a thickness greater than the average thickness T by more than 1 μm in a cleaning sheet according to at least one embodiment of the present invention.
[0026] Figure 8 A schematic cross-sectional view is provided to illustrate a conveying member with a cleaning function according to at least one embodiment of the present invention. Detailed Implementation
[0027] <<<<1. Cleaning tablets>>>>
[0028] The cleaning sheet according to at least one embodiment of the present invention includes a cleaning layer.
[0029] The cleaning sheet according to at least one embodiment of the present invention may consist of only a cleaning layer, or may include any other layers.
[0030] Figure 1 This is a schematic cross-sectional view illustrating a cleaning sheet according to at least one embodiment of the present invention. Figure 1 In this embodiment, the cleaning sheet 100 includes a cleaning layer 10 and a protective film 20. The protective film 20 may be configured for, for example, to protect the cleaning layer 10, and may be omitted depending on the purpose. That is, the cleaning sheet according to at least one embodiment of the present invention may include only the cleaning layer 10.
[0031] Figure 2 This is a schematic cross-sectional view illustrating a cleaning sheet according to at least one embodiment of the present invention. Figure 2 In this process, the cleaning sheet 100 includes a protective film 20, a cleaning layer 10, and a pressure-sensitive adhesive layer 30. The protective film 20 may be configured for purposes such as protecting the cleaning layer 10, and may be omitted depending on the purpose.
[0032] Figure 3 This is a schematic cross-sectional view illustrating a cleaning sheet according to at least one embodiment of the present invention. Figure 3 In this device, the cleaning sheet 100 includes a protective film 20, a cleaning layer 10, and a support 40. The protective film 20 may be configured for, for example, to protect the cleaning layer 10, and may be omitted depending on the purpose.
[0033] Figure 4This is a schematic cross-sectional view illustrating a cleaning sheet according to at least one embodiment of the present invention. Figure 4 In this device, the cleaning sheet 100 includes a protective film 20, a cleaning layer 10, a support 40, and a pressure-sensitive adhesive layer 30. The protective film 20 may be configured for, for example, to protect the cleaning layer 10, and may be omitted depending on the purpose.
[0034] The cleaning sheet according to at least one embodiment of the invention can have any suitable thickness depending on its composition (in particular, whether the sheet includes a support or a pressure-sensitive adhesive layer, and the thickness of the support or layer).
[0035] In a cleaning sheet according to at least one embodiment of the present invention, such as Figure 5 As shown, the direction from the end 11 of the surface 10a of the cleaning layer 10 toward its center 12 when viewed from the normal direction A relative to the surface 10a is defined as the center direction B.
[0036] In a cleaning sheet according to at least one embodiment of the present invention, such as Figure 5 As shown, the area occupied by the 10mm width from the end 11 toward the center direction B in the surface 10a of the cleaning layer 10 is defined as the end region C.
[0037] According to at least one embodiment of the present invention, the cleaning sheet can effectively suppress adsorption errors when the cleaning layer is adsorbed onto an adsorption stage or the like by appropriately adjusting the size of the raised portion (raised portion) formed in the periphery of the cleaning layer. In at least one embodiment of the present invention, as an indicator for appropriately adjusting the size of the raised portion, a schematic cross-sectional view through the center 12 of the cleaning layer 10 is provided. Figure 6 As shown, the difference (LT) between the maximum thickness L of the cleaning layer 10 in the normal direction A in the end region C and the average thickness T of the cleaning layer 10 in the normal direction A in the regions other than the end region C is used. As a result, the applicant has disclosed that when the difference is appropriately set, adsorption errors when the cleaning layer is adsorbed onto an adsorption stage or the like can be effectively suppressed.
[0038] That is, in the cleaning sheet according to at least one embodiment of the present invention, the relationship between the maximum thickness L of the cleaning layer 10 in the normal direction A in the end region C and the average thickness T of the cleaning layer 10 in the normal direction A in the regions other than the end region C is LT≤5μm, preferably LT≤4.5μm, more preferably LT≤4.0μm, even more preferably LT≤3.5μm, particularly preferably LT≤3.0μm, and most preferably LT≤2.5μm. When the difference LT falls within this range, adsorption error when the cleaning layer is adsorbed onto an adsorption stage or the like can be effectively suppressed. When the difference LT becomes larger and deviates from this range, when the cleaning layer is vacuum adsorbed onto an adsorption stage, such as a conveying device, it is presumed that a gap (albeit a small one) will be generated between the contact sealing member, such as a sealing strip, provided on the adsorption stage and the cleaning layer. This gap will cause damage to the sealing performance used to maintain the vacuum state, thereby generating adsorption error.
[0039] In a cleaning sheet according to at least one embodiment of the present invention, such as Figure 7 As shown, the width "d" of the portion of the cleaning layer 10 having a thickness greater than the average thickness T by more than 1 μm in the central direction B is preferably 4,000 μm or less, because this further enhances the effects of the present invention. When the width "d" of the portion of the cleaning layer having a thickness greater than the average thickness T by more than 1 μm in the central direction falls within this range, adsorption errors when the cleaning layer is adsorbed onto an adsorption stage or the like can be more effectively suppressed. If the width "d" of the portion of the cleaning layer having a thickness greater than the average thickness T by more than 1 μm in the central direction becomes larger and deviates from this range, when the cleaning layer is vacuum adsorbed onto an adsorption stage, such as a conveying device, a gap (albeit a small one) is presumably generated between the contact sealing member, such as a sealing strip, provided on the adsorption stage and the cleaning layer. This gap can impair the sealing performance used to maintain the vacuum state, thereby causing adsorption errors.
[0040] <<1-1. Cleaning Layer>>
[0041] The cleaning layer preferably comprises at least one selected from the group consisting of: polyimide resins; and polybenzoxazole resins, because the effects of the present invention can be achieved.
[0042] Polyimide resins are preferably polyimide resins incorporating soft segments, as this further enhances the effects of the invention. Polybenzoxazole resins are preferably polybenzoxazole resins incorporating soft segments, as this further enhances the effects of the invention. Therefore, the cleaning layer preferably comprises at least one selected from the group consisting of: polyimide resins incorporating soft segments; and polybenzoxazole resins incorporating soft segments, as this further enhances the effects of the invention. Without impairing the effects of the invention, any suitable soft segment can be used as the soft segment, as long as the soft segment is referred to as a so-called "soft segment" that imparts flexibility to the polymer.
[0043] In the cleaning layer, the content of at least one selected from the group consisting of polyimide resin and polybenzoxazole resin is preferably 50wt% to 100wt%, more preferably 70wt% to 100wt%, even more preferably 90wt% to 100wt%, particularly preferably 95wt% to 100wt%, and most preferably 98wt% to 100wt%, because the effects of the present invention can be fully expressed.
[0044] Any suitable polyimide resin may be used as a polyimide resin without impairing the effects of the present invention.
[0045] Polyimide resins are preferably polyimide resins obtained by imidizing polyamic acid, because the effects of the present invention can be further exhibited. Polyamic acid can generally be obtained by reacting a tetracarboxylic dianhydride component and a diamine component in any suitable organic solvent in a substantially equimolar ratio.
[0046] Examples of tetracarboxylic dianhydride components include 3,3′,4,4′-biphenyltetracarboxylic dianhydride, 2,2′,3,3′-biphenyltetracarboxylic dianhydride, 3,3′,4,4′-benzophenonetetracarboxylic dianhydride, 2,2′,3,3′-benzophenonetetracarboxylic dianhydride, 4,4′-oxophthalic dianhydride, 2,2-bis(2,3-dicarboxyphenyl)hexafluoropropane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (6FDA), bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)sulfone dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, pyromellitic dianhydride, and ethylene glycol bistrimellitic dianhydride. These components can be used alone or in combination.
[0047] Examples of diamine components include diamine compounds having at least two ends, each having an amine structure and a polyether structure (hereinafter sometimes referred to as "PE diamine compounds"), aliphatic diamines, and aromatic diamines. Among these, PE diamine compounds are preferred as diamine components because they can further enhance the effects of the present invention.
[0048] Any suitable compound can be used as a PE diamine compound, provided that the compound has a polyether structure and at least two ends, each having an amine structure. Examples of PE diamine compounds include terminal diamines having a polypropylene glycol structure, terminal diamines having a polyethylene glycol structure, terminal diamines having a polytetramethylene glycol structure, and terminal diamines having multiple of these structures. More specific examples of PE diamine compounds are PE diamine compounds having at least two ends, each having an amine structure, prepared from ethylene oxide, propylene oxide, polytetramethylene glycol, polyamine, or mixtures thereof. These PE diamine compounds each introduce a polyether structure as a soft segment therein, and thus can further exhibit the effects of the present invention. That is, the PE diamine compound is a polyimide resin in which a soft segment is introduced.
[0049] Examples of aliphatic diamines include ethylenediamine, hexamethylenediamine, 1,8-,1,10-diaminodecane, 1,12-diaminododecane, 4,9-dioxa-1,12-diaminododecane, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane (α,ω-bisaminopropyltetramethyldisiloxane). The molecular weight of the aliphatic diamine is preferably 50 to 1,000,000, more preferably 100 to 30,000.
[0050] Examples of aromatic diamines include 4,4′-diaminodiphenyl ether, 3,4′-diaminodiphenyl ether, 3,3′-diaminodiphenyl ether, m-phenylenediamine, p-phenylenediamine, 4,4′-diaminodiphenylpropane, 3,3′-diaminodiphenylmethane, 4,4′-diaminodiphenyl sulfide, 3,3′-diaminodiphenyl sulfide, 4,4′-diaminodiphenyl sulfone, 3,3′-diaminodiphenyl sulfone, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)-2,2-dimethylpropane, and 4,4′-diaminobenzophenone.
[0051] Examples of organic solvents used for the reaction between tetracarboxylic dianhydrides and diamines include N,N-dimethylacetamide, N-methyl-2-pyrrolidone, and N,N-dimethylformamide. To adjust the solubility of raw materials, etc., a nonpolar solvent (e.g., toluene or xylene) may be used in conjunction.
[0052] The preferred reaction temperature between tetracarboxylic acid dianhydride and diamine is 40°C or higher, more preferably 50°C to 150°C.
[0053] The imidization of polyamic acid is typically carried out by heat treatment under an inert atmosphere (typically a vacuum or nitrogen atmosphere). The heat treatment temperature is preferably 150°C or higher, more preferably 180°C to 450°C.
[0054] Polybenzoxazole resins are resins with heat resistance and insulation properties. The preferred polybenzoxazole resin is a modified polybenzoxazole obtained by introducing soft segments into the polybenzoxazole, as this allows the effects of the present invention to be achieved. That is, the modified polybenzoxazole is a polybenzoxazole resin in which soft segments have been introduced.
[0055] Without impairing the effects of the present invention, any suitable soft segment can be used as a soft segment in modified polybenzoxazole, as long as the soft segment is referred to as a so-called "soft segment" that imparts flexibility to the polymer. Among such soft segments, those having components selected from -(OR) n -and-(O-COO-R) n At least one of the repetitive skeleton segments represented in - is preferred because it further enhances the effects of the invention. The skeleton that can be incorporated into the soft segment - (OR) n The number of types can be only one, or it can be two or more. It can be incorporated into the skeleton (O-COO-R) of the soft chain segment. n - The number of types can be only one, or it can be two or more.
[0056] Selected from -(OR) n -and-(O-COO-R) n In at least one of the repeating skeletons represented by "-", R represents an alkylene group having 2 to 18 carbon atoms, and "n" represents a number from 1 to 100. R preferably represents an alkylene group having 2 to 12 carbon atoms, more preferably an alkylene group having 3 to 10 carbon atoms, even more preferably an alkylene group having 3 to 6 carbon atoms, and particularly preferably an alkylene group having 3 or 4 carbon atoms. "n" preferably represents a number from 5 to 90, more preferably a number from 10 to 70, and particularly preferably a number from 10 to 50.
[0057] Modified polybenzoxazole can preferably be achieved by using a compound selected from -(OR) n -and-(O-COO-R) n The compound (S) is prepared by means of at least one of the repeating skeletons represented in the diagram. This compound (S) preferably has a functional group at each of its two ends that reacts with chloride (-Cl). Examples of such functional groups include amino, substituted amino, and hydroxyl groups.
[0058] Examples of compounds (S) include H2N-R 1 -(OR) n -R 2 -NH2、H2N-R 1 -(O-COO-R) n -R 2 -NH2, HO-R 1 -(OR) n -R 2 -OH and HO-R 1 -(O-COO-R) n -R 2 -OH. Here, R 1 and R 2 Each can independently represent a single bond or an alkylene group having 1 to 18 carbon atoms (preferably 2 to 12 carbon atoms, more preferably 3 to 10 carbon atoms, even more preferably 3 to 6 carbon atoms, particularly preferably 3 or 4 carbon atoms). As described above, the skeleton -(OR) n - can be of only one type, or can be two or more types, and the skeleton is -(O-COO-R). n - The number of species can be only one, or it can be two. That is, for example, when using H2N-R 1 -(OR) n -R 2 When -NH2 is used as an instance description, the skeleton is -(OR) n -Can be derived from -(O-CH2-CH(CH3)) x -(O-CH2-CH2) y -(O-CH2-CH(CH3)) z - indicates (where "x", "y", and "z" each independently represent a number from 1 to 100).
[0059] The molecular weight of compound (S) is preferably 300 to 3,500, more preferably 500 to 3,000, even more preferably 600 to 2,500, and particularly preferably 800 to 2,200, because this can further enhance the effects of the present invention.
[0060] The blending ratio (sometimes referred to as the "soft segment ratio") of compound (S) relative to the total amount of amine component used to manufacture modified polybenzoxazole having soft segments is preferably 2 mol% to 40 mol%, more preferably 3 mol% to 35 mol%, even more preferably 5 mol% to 32 mol%, particularly preferably 8 mol% to 31 mol%, and most preferably 10 mol% to 30 mol%, because this can further enhance the effects of the present invention.
[0061] An example of a method for manufacturing modified polybenzoxazole using compound (S) is a method comprising the following steps: 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol), a soft segment, pyridine, and N-methyl-2-pyrrolidone are placed into a removable flask equipped with a stirrer; the mixture is stirred at room temperature until all materials are completely dissolved; then trimethylchlorosilane is added dropwise to the flask over a predetermined time (e.g., 1 minute); the mixture is stirred at a predetermined temperature (e.g., room temperature) for a predetermined time (e.g., 60 minutes); then 4,4′-bis(chlorocarbonyl)diphenyl ether is slowly added to the flask over a predetermined time (e.g., 5 minutes); the mixture is stirred at a predetermined temperature (e.g., room temperature) for a predetermined time (e.g., 5 minutes). The resulting synthetic solution is added dropwise to a predetermined amount (e.g., 2 L) of ion-exchanged water; the precipitate is dried at a predetermined temperature (e.g., 100 °C) for a predetermined time (e.g., 24 hours); a predetermined amount (e.g., 4 times the amount) of N-methyl-2-pyrrolidone is added to the dried precipitate to redissolve the precipitate, thereby obtaining a modified polybenzoxazole varnish; the modified polybenzoxazole varnish is coated onto the mirror surface of a silicon wafer by spin coating; the varnish is heated at a predetermined temperature (e.g., 150 °C) for a predetermined time (e.g., 30 minutes) to remove N-methyl-2-pyrrolidone; and the residue is then heated under vacuum at a predetermined temperature (e.g., 300 °C) for a predetermined time (e.g., 2 hours).
[0062] Without impairing the effects of the invention, any other suitable components may be incorporated into the cleaning layer. Examples of such other components include: heat-resistant resins other than polyimide and polybenzoxazole resins; surfactants; plasticizers; antioxidants; conductivity imparting agents; ultraviolet absorbers; and light stabilizers.
[0063] The thickness of the cleaning layer is preferably 1 μm to 100 μm, more preferably 1 μm to 50 μm, even more preferably 1 μm to 30 μm, particularly preferably 1 μm to 20 μm, and most preferably 2 μm to 10 μm. When the thickness of the cleaning layer falls within this range, the effects of the present invention can be further demonstrated.
[0064] The cleaning layer preferably has substantially no adhesive force. More specifically, for example, cleaning layers formed of adhesive substances and cleaning layers formed by fixing with pressure-sensitive adhesive tape are not included in the cleaning layer of at least one embodiment of the invention. When the cleaning sheet according to at least one embodiment of the invention includes a cleaning layer that has substantially adhesive force, the cleaning layer and, for example, the conveying device in a substrate processing apparatus, will adhere too strongly at their contact points, making it impossible for the layer and the device to separate from each other. As a result, problems arise such as unreliable substrate conveying and damage to the conveying device.
[0065] As described above, it is preferable that the cleaning layer has essentially no adhesive force. Specifically, the 180° peel adhesion force A of the layer relative to the mirror surface of the silicon wafer, as defined by JIS-Z-0237, is preferably less than 0.20 N / 10 mm, more preferably 0.01 N / 10 mm to 0.10 N / 10 mm. When the 180° peel adhesion force A of the cleaning layer relative to the mirror surface of the silicon wafer, as defined by JIS-Z-0237, falls within this range, the cleaning layer has essentially no adhesive force, and thus the pressure-sensitive adhesion between the cleaning layer and, for example, the transport device in the substrate processing apparatus can be reduced. As a result, the substrate can be transported reliably, and the transport device can be transported with almost no damage.
[0066] The 180° peel adhesion force B of the cleaning layer relative to the mirror surface of the simulating wafer, as defined by JIS-Z-0237, is preferably 10 N / 10 mm or more, more preferably 15 N / 10 mm or more, even more preferably 20 N / 10 mm or more, particularly preferably 25 N / 10 mm or more, and most preferably 30 N / 10 mm or more. When the 180° peel adhesion force B of the cleaning layer relative to the mirror surface of the simulating wafer, as defined by JIS-Z-0237, falls within this range, for example, the adhesion between the cleaning layer and the transport component such as the simulating wafer becomes higher, and therefore the cleaning layer is difficult to peel off from the transport component such as the simulating wafer during cleaning.
[0067] For example, the 180° peel adhesion force B of the cleaning layer relative to the mirror surface of the simulating wafer, as defined by JIS-Z-0237, can be measured as follows: The cleaning layer is formed on the mirror surface of the silicon wafer used as the simulating wafer, and its peel adhesion force is measured in accordance with JIS-Z-0237.
[0068] <<1-2. Support Structure>>
[0069] The cleaning sheet according to at least one embodiment of the present invention may include a support. The support may be a single layer or a multilayer structure.
[0070] Within the scope of not impairing the effects of the present invention, any suitable thickness can be used as the thickness of the support. This thickness is preferably 500 μm or less, more preferably 1 μm to 400 μm, even more preferably 1 μm to 300 μm, particularly preferably 1 μm to 200 μm, and most preferably 1 μm to 100 μm.
[0071] Any suitable support may be used as the support without impairing the effects of the invention. Examples of such supports include membranes made of plastics, engineering plastics, and super-engineering plastics. Specific examples of plastics, engineering plastics, and super-engineering plastics include polyimide, polyethylene, polyethylene terephthalate, acetyl cellulose, polycarbonate, polypropylene, and polyamide.
[0072] The material of the support can be appropriately selected according to the purpose.
[0073] The forming method of the support can be appropriately selected according to the purpose.
[0074] The surface of the support can undergo conventional surface treatments, such as chemical or physical treatments like chromic acid treatment, ozone exposure, flame exposure, high-voltage electric shock exposure, and ionizing radiation treatment, or be treated with an undercoating agent to improve its adhesion and retention relative to adjacent layers.
[0075] <<1-3. Pressure-sensitive adhesive layer>>
[0076] The cleaning sheet according to at least one embodiment of the present invention may include a pressure-sensitive adhesive layer. Any suitable material may be used as the material for such a pressure-sensitive adhesive layer without impairing the effects of the invention. For example, acrylic pressure-sensitive adhesives, silicone pressure-sensitive adhesives, rubber pressure-sensitive adhesives, or polyurethane pressure-sensitive adhesives may be used as the material for such a pressure-sensitive adhesive layer.
[0077] The pressure-sensitive adhesive layer is provided for, for example, attaching the cleaning sheet to the mirror surface of the simulated wafer. Therefore, a cleaning sheet according to at least one embodiment of the invention is attached to the simulated wafer used as a transport member, and thus a transport member with a cleaning function according to at least one embodiment of the invention can be obtained.
[0078] The 180° peel adhesion force C of the pressure-sensitive adhesive layer relative to the mirror surface of the simulating wafer, as defined by JIS-Z-0237, is preferably 10 N / 10 mm or more, more preferably 15 N / 10 mm or more, even more preferably 20 N / 10 mm or more, particularly preferably 25 N / 10 mm or more, and most preferably 30 N / 10 mm or more. When the 180° peel adhesion force C of the pressure-sensitive adhesive layer relative to the mirror surface of the simulating wafer, as defined by JIS-Z-0237, falls within this range, for example, the adhesion between the pressure-sensitive adhesive layer and the simulating wafer becomes higher, and therefore the cleaning pad is difficult to peel off from the simulating wafer during cleaning.
[0079] The thickness of the pressure-sensitive adhesive layer is preferably 1μm to 200μm, more preferably 2μm to 100μm, even more preferably 3μm to 80μm, particularly preferably 4μm to 60μm, and most preferably 5μm to 50μm.
[0080] <<1-4. Protective Film>>
[0081] A cleaning sheet according to at least one embodiment of the present invention may include a protective film for protecting, for example, a cleaning layer, a support, or a pressure-sensitive adhesive layer. The protective film may be peeled off at appropriate stages.
[0082] Any suitable membrane may be used as a protective membrane without impairing the effects of the present invention. Examples of materials for such membranes include polyolefins such as polyethylene, polypropylene, polybutene, polybutadiene, and polymethylpentene; polyvinyl chloride; vinyl chloride copolymers; polyethylene terephthalate; polybutylene terephthalate; polyurethane; ethylene vinyl acetate copolymers; ionomer resins; ethylene-(meth)acrylic acid copolymers; ethylene-(meth)acrylic acid copolymers; polystyrene; polycarbonate; polyimide; and fluoropolymers.
[0083] Without impairing the effects of the invention, the protective film may be subjected to any suitable peeling treatment. Peeling treatment is typically performed using a peeling agent. Examples of peeling agents may include silicone-based peeling agents, long-chain alkyl-based peeling agents, fluorinated peeling agents, fatty acid amide-based peeling agents, and silica-based peeling agents.
[0084] The thickness of the protective film is preferably 1μm to 100μm.
[0085] The method of forming the protective film is appropriately selected according to the purpose, and the film can be formed by, for example, injection molding, extrusion molding, or blow molding.
[0086] <<1-5. Manufacturing Method of Cleaning Tablets>>
[0087] Within the scope of not impairing the effects of the present invention, any suitable manufacturing method may be used as a method for manufacturing a cleaning sheet according to at least one embodiment of the present invention. Examples of such manufacturing methods include: (1) a method comprising casting a varnish solution for the cleaning layer onto a support or conveying member, uniformly forming the solution into a film using a spin coater or the like, and then heating the film to directly form a cleaning layer on the support or conveying member; and (2) a method comprising, for example, attaching a pressure-sensitive adhesive film (a product obtained by providing a cleaning layer on one side of a label support and a conventional pressure-sensitive adhesive layer on the other side) as a constituent material of a label and a reinforcement to an insulator to form a laminate comprising an insulator and a pressure-sensitive adhesive film, then punching only the pressure-sensitive adhesive film of the laminate into the shapes of the label and / or the reinforcement simultaneously or separately, and peeling off any unwanted pressure-sensitive adhesive film from the insulator.
[0088] Because it can further demonstrate the effects of the present invention, a preferred example of a method for manufacturing a cleaning sheet according to at least one embodiment of the present invention is a method for manufacturing a cleaning sheet according to at least one embodiment of the present invention, the method comprising: applying a varnish solution of the cleaning layer onto a support or conveying member using a spin coater to form a film; allowing the film to stand as needed; and heating and / or drying the film as needed to form a cleaning layer on the support or conveying member.
[0089] The viscosity of the varnish solution for the cleaning layer is preferably 100 mPa·s to 2,000 mPa·s, more preferably 300 mPa·s to 1,500 mPa·s, and even more preferably 500 mPa·s to 1,200 mPa·s, because this can further enhance the effects of the present invention.
[0090] When forming a film by applying the varnish solution of the cleaning layer onto the support or conveying component using a spin coater, the rotation speed is preferably 400 rpm or more, more preferably 600 rpm or more, even more preferably 800 rpm or more, even more preferably 1,000 rpm or more, even more preferably 1,500 rpm or more, particularly preferably 2,000 rpm or more, and most preferably 3,000 rpm or more, because this further enhances the effects of the present invention. The upper limit of the rotation speed is preferably 6,000 rpm or less, because this further enhances the effects of the present invention.
[0091] The rotation time for forming a film by applying the varnish solution of the cleaning layer to the support or conveying component using a spin coater is preferably 5 to 200 seconds, more preferably 10 to 150 seconds, or even more preferably 20 to 60 seconds, because this can further demonstrate the effects of the present invention.
[0092] In a method for manufacturing a cleaning sheet according to at least one embodiment of the present invention, when a varnish solution for the cleaning layer is applied to a support or conveying member using a spin coater to form a film, and then the film is allowed to stand, the varnish solution can be further smoothed on the support or conveying member. The standing time of the film is preferably 5 to 1,000 seconds, more preferably 30 to 600 seconds, and even more preferably 100 to 400 seconds, because this further enhances the effects of the present invention.
[0093] In a method for manufacturing a cleaning sheet according to at least one embodiment of the present invention, after a varnish solution for the cleaning layer is applied to a support or conveying member using a spin coater to form a film, the film may be heated and / or dried. The temperature for heating or drying is preferably 50°C to 200°C, more preferably 80°C to 150°C, because this further enhances the effects of the present invention. The time for heating or drying is preferably 100 seconds to 900 seconds, more preferably 300 seconds to 900 seconds, and even more preferably 600 seconds to 900 seconds, because this further enhances the effects of the present invention.
[0094] <<<<2. Conveying components with cleaning functions>>>>
[0095] A conveying member with a cleaning function according to at least one embodiment of the present invention includes a cleaning sheet and a conveying member according to at least one embodiment of the present invention.
[0096] Figure 8This is a schematic cross-sectional view illustrating a conveying member with a cleaning function according to at least one embodiment of the present invention. Figure 8 In this process, the delivery component 300 with cleaning function includes a cleaning sheet 100 and a delivery component 200. When the cleaning sheet 100 includes a pressure-sensitive adhesive layer, it is preferable that the outermost layer of the cleaning sheet 100 on the delivery component 200 side is a pressure-sensitive adhesive layer.
[0097] Any suitable transport member may be used as a transport member without impairing the effects of the present invention. Examples of such transport members include: semiconductor wafers (e.g., silicon wafers); substrates for flat panel displays such as LCDs or PDPs; optical discs; and MR heads. Among these transport members, semiconductor wafers (e.g., silicon wafers) are typically given as examples of transport members when the transport member is intended to clean the apparatus used for transporting wafers within a substrate processing apparatus.
[0098] Example
[0099] The invention will now be described in more detail by way of examples and comparative examples. However, the invention is by no means limited thereto. In the following description, unless otherwise stated, the terms "parts" and "%" are by weight.
[0100] <Methods for measuring bulge size>
[0101] The bulge height and bulge width were measured using a stylus-type surface roughness measuring device (manufactured by Veeco Instruments Inc., Dektak 8). Measurements were performed by moving a diamond stylus (with a tip curvature of 2.5 μm) at a measuring speed of 200 μm / s over a 10 mm measurement range. The measurement starting point was defined as a point 10 mm from the inner edge of the resin layer on the wafer, and measurements were taken within a 10 mm radius from this starting point towards its outer perimeter. The maximum height obtained during the measurement was defined as the bulge height, and the bulge width was defined as the distance from a point 0.5 μm higher than the starting point to the edge of the resin layer.
[0102] <Evaluation of Adsorption Error>
[0103] The vacuum adsorption stage is circular with a diameter of 300 mm and has equally spaced circular protrusions on its surface, each protrusion having a diameter of 300 μm and a height of 300 μm. The platform has a sealing strip with a height of 300 μm and a width of 300 μm at a position 3 mm from its outer edge.
[0104] A cleaning-function conveying component is mounted on a vacuum adsorption stage, and the air pressure around the component is reduced to -42,000 Pa. Components showing an adsorption pressure of -42,000 Pa or higher but less than -35,000 Pa are rated as good (indicated by the symbol ○), components showing an adsorption pressure of -35,000 Pa or higher but less than -30,000 Pa are rated as average (indicated by the symbol △), and components showing an adsorption pressure of -30,000 Pa or higher are rated as poor (indicated by the symbol ×).
[0105] [Example 1]
[0106] (Preparation of modified polybenzoxazole varnish)
[0107] 43.8 g of 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol), 64.4 g of H2N-CH(CH3)-CH2-(O-CH(CH3)-CH2)2-(O-CH2CH2CH2CH2)9-(O-CH2-CH(CH3))3-NH2 (trade name: “ELASTAMINE RT-1000”, manufactured by Huntsman Corporation, molecular weight: 1,000), 47.0 g of pyridine, and 600 g of N-methyl-2-pyrrolidone were placed in a detachable flask equipped with a stirrer, and the mixture was stirred at room temperature until 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol) and ELASTAMINE RT-1000 were completely dissolved. Then, 32.6 g of trimethylchlorosilane was added dropwise to the flask over 10 minutes, and the mixture was stirred at room temperature for 60 minutes. Then, 54.3 g of 4,4′-bis(chlorocarbonyl)diphenyl ether was slowly added to the flask over 10 minutes, and the mixture was stirred at room temperature for 1 hour.
[0108] The resulting synthetic solution was added dropwise to 10 L of ion-exchanged water, and the resulting precipitate was dried at 120 °C for 4 hours. Four times the amount of N-methyl-2-pyrrolidone was added to the dried precipitate to redissolve it. Thus, a varnish of modified polybenzoxazole (1) was obtained. The viscosity of the obtained varnish of modified polybenzoxazole (1) was 540 mPa·s.
[0109] (Including the manufacture and evaluation of conveyor components with cleaning functions in the cleaning layer)
[0110] The obtained modified polybenzoxazole (1) varnish was applied to the mirror surface of a 12-inch silicon wafer using a spin coater (manufactured by Tokyo Electron Limited, ACT-12, 4,000 rpm, spin time = 30 seconds) and left to stand for 300 seconds. Then, the varnish was heated at 100°C for 10 minutes to remove N-methyl-2-pyrrolidone. The residue was then heated under vacuum at 280°C for 2 hours. Thus, a clean-functional transport member (1) comprising a clean layer (1) with a thickness of 2.8 μm was obtained. The clean-functional transport member (1) comprises a clean sheet (1) formed from the clean layer (1) and a silicon wafer used as the transport member.
[0111] The results are shown in Table 1.
[0112] [Example 2]
[0113] (Preparation of modified polybenzoxazole varnish)
[0114] 54.0 g of 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol) and 66 g of H2N-CH(CH3)-(O-CH2-CH(CH3)) were added. n -NH2 (trade name: "JEFFAMINE D-2000", manufactured by Huntsman Corporation, molecular weight: 2,000, n = approx. 33), 47.0 g of pyridine, and 600 g of N-methyl-2-pyrrolidone were placed in a detachable flask equipped with a stirrer, and the mixture was stirred at room temperature until 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol) and JEFFAMINED-2000 were completely dissolved. Then, 48.0 g of trimethylchlorosilane was added dropwise to the flask over 10 minutes, and the mixture was stirred at room temperature for 60 minutes. Next, 55.2 g of 4,4′-bis(chlorocarbonyl)diphenyl ether was slowly added to the flask over 10 minutes, and the mixture was stirred at room temperature for 1 hour.
[0115] The resulting synthetic solution was added dropwise to 10 L of ion-exchanged water, and the resulting precipitate was dried at 120 °C for 4 hours. Four times the amount of N-methyl-2-pyrrolidone was added to the dried precipitate to redissolve it. Thus, a varnish of modified polybenzoxazole (2) was obtained. The viscosity of the obtained varnish of modified polybenzoxazole (2) was 580 mPa·s.
[0116] (Including the manufacture and evaluation of conveyor components with cleaning functions in the cleaning layer)
[0117] The modified polybenzoxazole (2) varnish was applied to the mirror surface of a 12-inch silicon wafer using a spin coater (manufactured by Tokyo Electron Limited, ACT-12, 1,000 rpm, spin time = 30 seconds) and left to stand for 300 seconds. The varnish was then heated at 100°C for 10 minutes to remove N-methyl-2-pyrrolidone. The residue was then heated under vacuum at 280°C for 2 hours. Thus, a clean-functional transport member (2) comprising a clean layer (2) with a thickness of 2.2 μm was obtained. The clean-functional transport member (2) comprises a clean sheet (2) formed from the clean layer (2) and a silicon wafer used as the transport member.
[0118] The results are shown in Table 1.
[0119] [Example 3]
[0120] (Preparation of modified polybenzoxazole varnish)
[0121] 43.8 g of 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol), 64.4 g of H2N-CH(CH3)-CH2-(O-CH(CH3)-CH2)2-(O-CH2CH2CH2CH2)9-(O-CH2-CH(CH3))3-NH2 (trade name: “ELASTAMINE RT-1000”, manufactured by Huntsman Corporation, molecular weight: 1,000), 47.0 g of pyridine, and 600 g of N-methyl-2-pyrrolidone were placed in a detachable flask equipped with a stirrer, and the mixture was stirred at room temperature until 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol) and ELASTAMINE RT-1000 were completely dissolved. Then, 32.6 g of trimethylchlorosilane was added dropwise to the flask over 10 minutes, and the mixture was stirred at room temperature for 60 minutes. Then, 54.3 g of 4,4′-bis(chlorocarbonyl)diphenyl ether was slowly added to the flask over 10 minutes, and the mixture was stirred at room temperature for 2 hours.
[0122] The resulting synthetic solution was added dropwise to 10 L of ion-exchanged water, and the resulting precipitate was dried at 120 °C for 4 hours. Four times the amount of N-methyl-2-pyrrolidone was added to the dried precipitate to redissolve it. Thus, a varnish of modified polybenzoxazole (3) was obtained. The viscosity of the obtained varnish of modified polybenzoxazole (3) was 980 mPa·s.
[0123] (Including the manufacture and evaluation of conveyor components with cleaning functions in the cleaning layer)
[0124] The modified polybenzoxazole (3) varnish was applied to the mirror surface of a 12-inch silicon wafer using a spin coater (manufactured by Tokyo Electron Limited, ACT-12, 2,000 rpm, spin time = 30 seconds) and left to stand for 300 seconds. The varnish was then heated at 100°C for 10 minutes to remove N-methyl-2-pyrrolidone. The residue was then heated under vacuum at 280°C for 2 hours. Thus, a clean-functional transport member (3) comprising a clean layer (3) with a thickness of 5.4 μm was obtained. The clean-functional transport member (3) comprises a clean sheet (3) formed from the clean layer (3) and a silicon wafer used as the transport member.
[0125] The results are shown in Table 1.
[0126] [Example 4]
[0127] (Preparation of modified polybenzoxazole varnish)
[0128] 43.8 g of 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol), 64.4 g of H2N-CH(CH3)-CH2-(O-CH(CH3)-CH2)2-(O-CH2CH2CH2CH2)9-(O-CH2-CH(CH3))3-NH2 (trade name: “ELASTAMINE RT-1000”, manufactured by Huntsman Corporation, molecular weight: 1,000), 47.0 g of pyridine, and 600 g of N-methyl-2-pyrrolidone were placed in a detachable flask equipped with a stirrer, and the mixture was stirred at room temperature until 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol) and ELASTAMINE RT-1000 were completely dissolved. Then, 32.6 g of trimethylchlorosilane was added dropwise to the flask over 10 minutes, and the mixture was stirred at room temperature for 60 minutes. Then, 54.3 g of 4,4′-bis(chlorocarbonyl)diphenyl ether was slowly added to the flask over 10 minutes, and the mixture was stirred at room temperature for 2 hours.
[0129] The resulting synthetic solution was added dropwise to 10 L of ion-exchanged water, and the resulting precipitate was dried at 120 °C for 4 hours. Four times the amount of N-methyl-2-pyrrolidone was added to the dried precipitate to redissolve it. Thus, a varnish of modified polybenzoxazole (4) was obtained. The viscosity of the obtained varnish of modified polybenzoxazole (4) was 780 mPa·s.
[0130] (Including the manufacture and evaluation of conveyor components with cleaning functions in the cleaning layer)
[0131] The obtained modified polybenzoxazole (4) varnish was applied to the mirror surface of a 12-inch silicon wafer using a spin coater (manufactured by Tokyo Electron Limited, ACT-12, 1,000 rpm, spin time = 30 seconds) and left to stand for 300 seconds. The varnish was then heated at 100°C for 10 minutes to remove N-methyl-2-pyrrolidone. The residue was then heated under vacuum at 280°C for 2 hours. Thus, a clean-functional transport member (4) comprising a clean layer (4) with a thickness of 5.0 μm was obtained. The clean-functional transport member (4) comprises a clean sheet (4) formed from the clean layer (4) and a silicon wafer used as the transport member.
[0132] The results are shown in Table 1.
[0133] [Example 5]
[0134] (Preparation of modified polybenzoxazole varnish)
[0135] 43.8 g of 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol), 64.4 g of H2N-CH(CH3)-CH2-(O-CH(CH3)-CH2)2-(O-CH2CH2CH2CH2)9-(O-CH2-CH(CH3))3-NH2 (trade name: “ELASTAMINE RT-1000”, manufactured by Huntsman Corporation, molecular weight: 1,000), 47.0 g of pyridine, and 600 g of N-methyl-2-pyrrolidone were placed in a detachable flask equipped with a stirrer, and the mixture was stirred at room temperature until 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol) and ELASTAMINE RT-1000 were completely dissolved. Then, 32.6 g of trimethylchlorosilane was added dropwise to the flask over 10 minutes, and the mixture was stirred at room temperature for 60 minutes. Then, 54.3 g of 4,4′-bis(chlorocarbonyl)diphenyl ether was slowly added to the flask over 10 minutes, and the mixture was stirred at room temperature for 2 hours.
[0136] The resulting synthetic solution was added dropwise to 10 L of ion-exchanged water, and the resulting precipitate was dried at 120 °C for 4 hours. Four times the amount of N-methyl-2-pyrrolidone was added to the dried precipitate to redissolve it. Thus, a varnish of modified polybenzoxazole (5) was obtained. The viscosity of the obtained varnish of modified polybenzoxazole (5) was 840 mPa·s.
[0137] (Including the manufacture and evaluation of conveyor components with cleaning functions in the cleaning layer)
[0138] The obtained modified polybenzoxazole (5) varnish was applied to the mirror surface of a 12-inch silicon wafer using a spin coater (manufactured by Tokyo Electron Limited, ACT-12, 1,000 rpm, spin time = 30 seconds) and left to stand for 300 seconds. Then, the varnish was heated at 100°C for 10 minutes to remove N-methyl-2-pyrrolidone. The residue was then heated under vacuum at 280°C for 2 hours. Thus, a clean-functional transport member (5) comprising a clean layer (5) with a thickness of 6.2 μm was obtained. The clean-functional transport member (5) comprises a clean sheet (5) formed from the clean layer (5) and a silicon wafer used as the transport member.
[0139] The results are shown in Table 1.
[0140] [Example 6]
[0141] (Preparation of modified polybenzoxazole varnish)
[0142] 43.8 g of 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol), 64.4 g of H2N-CH(CH3)-CH2-(O-CH(CH3)-CH2)2-(O-CH2CH2CH2CH2)9-(O-CH2-CH(CH3))3-NH2 (trade name: “ELASTAMINE RT-1000”, manufactured by Huntsman Corporation, molecular weight: 1,000), 47.0 g of pyridine, and 600 g of N-methyl-2-pyrrolidone were placed in a detachable flask equipped with a stirrer, and the mixture was stirred at room temperature until 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol) and ELASTAMINE RT-1000 were completely dissolved. Then, 32.6 g of trimethylchlorosilane was added dropwise to the flask over 10 minutes, and the mixture was stirred at room temperature for 60 minutes. Then, 54.3 g of 4,4′-bis(chlorocarbonyl)diphenyl ether was slowly added to the flask over 10 minutes, and the mixture was stirred at room temperature for 3 hours.
[0143] The resulting synthetic solution was added dropwise to 10 L of ion-exchanged water, and the resulting precipitate was dried at 120 °C for 4 hours. Four times the amount of N-methyl-2-pyrrolidone was added to the dried precipitate to redissolve it. Thus, a varnish of modified polybenzoxazole (6) was obtained. The viscosity of the obtained varnish of modified polybenzoxazole (6) was 1,230 mPa·s.
[0144] (Including the manufacture and evaluation of conveyor components with cleaning functions in the cleaning layer)
[0145] The obtained modified polybenzoxazole (6) varnish was applied to the mirror surface of a 12-inch silicon wafer using a spin coater (manufactured by Tokyo Electron Limited, ACT-12, 1,000 rpm, spin time = 30 seconds) and left to stand for 300 seconds. The varnish was then heated at 100°C for 10 minutes to remove N-methyl-2-pyrrolidone. The residue was then heated under vacuum at 280°C for 2 hours. Thus, a clean-functional transport member (6) comprising a clean layer (6) with a thickness of 5.8 μm was obtained. The clean-functional transport member (6) comprises a clean sheet (6) formed from the clean layer (6) and a silicon wafer used as the transport member.
[0146] The results are shown in Table 1.
[0147] [Example 7]
[0148] (Manufacturing of polyimide varnish)
[0149] 51.0 g of 4,4′-diaminodiphenyl ether and 89 g of H2N-CH(CH3)-(O-CH2-CH(CH3)) were added. n -NH2 (trade name: "JEFFAMINE D-4000", manufactured by Huntsman Corporation, molecular weight: 4,000, n = about 68), 1,000 g of N-methyl-2-pyrrolidone were placed in a detachable flask equipped with a stirrer, and the mixture was stirred at room temperature until 4,4′-diaminodiphenyl ether and JEFFAMINE D-4000 were completely dissolved. Then, 60 g of pyromellitic anhydride was slowly added to the flask over 10 minutes, and the mixture was stirred at room temperature for 1 hour. The mixture was heated to 70°C and stirred for 4 hours to provide a varnish of polyimide (7). The resulting varnish of polyimide (7) had a viscosity of 1,000 mPa·s.
[0150] (Including the manufacture and evaluation of conveyor components with cleaning functions in the cleaning layer)
[0151] The obtained polyimide (7) varnish was applied to the mirror surface of a 12-inch silicon wafer using a spin coater (manufactured by Tokyo Electron Limited, ACT-12, 1,000 rpm, spin time = 30 seconds) and left to stand for 300 seconds. The varnish was then heated at 100°C for 2 minutes to remove N-methyl-2-pyrrolidone. The residue was then heated under vacuum at 280°C for 2 hours. Thus, a clean-functional transport member (7) comprising a clean layer (7) with a thickness of 7.0 μm was obtained. The clean-functional transport member (7) comprises a clean sheet (7) formed from the clean layer (7) and a silicon wafer used as the transport member.
[0152] The results are shown in Table 1.
[0153] [Comparative Example 1]
[0154] (Preparation of modified polybenzoxazole varnish)
[0155] 43.8 g of 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol), 64.4 g of H2N-CH(CH3)-CH2-(O-CH(CH3)-CH2)2-(O-CH2CH2CH2CH2)9-(O-CH2-CH(CH3))3-NH2 (trade name: “ELASTAMINE RT-1000”, manufactured by Huntsman Corporation, molecular weight: 1,000), 47.0 g of pyridine, and 600 g of N-methyl-2-pyrrolidone were placed in a detachable flask equipped with a stirrer, and the mixture was stirred at room temperature until 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol) and ELASTAMINE RT-1000 were completely dissolved. Then, 32.6 g of trimethylchlorosilane was added dropwise to the flask over 10 minutes, and the mixture was stirred at room temperature for 60 minutes. Then, 54.3 g of 4,4′-bis(chlorocarbonyl)diphenyl ether was slowly added to the flask over 10 minutes, and the mixture was stirred at room temperature for 6 hours.
[0156] The resulting synthetic solution was added dropwise to 10 L of ion-exchanged water, and the resulting precipitate was dried at 120 °C for 4 hours. Four times the volume of N-methyl-2-pyrrolidone was added to the dried precipitate to redissolve it. Thus, a varnish of modified polybenzoxazole (C1) was obtained. The viscosity of the obtained varnish of modified polybenzoxazole (C1) was 1,740 mPa·s.
[0157] (Including the manufacture and evaluation of conveyor components with cleaning functions in the cleaning layer)
[0158] The modified polybenzoxazole (C1) varnish was applied to the mirror surface of a 12-inch silicon wafer using a spin coater (manufactured by Tokyo Electron Limited, ACT-12, 1,000 rpm, spin time = 30 seconds) and left to stand for 300 seconds. The varnish was then heated at 100°C for 10 minutes to remove N-methyl-2-pyrrolidone. The residue was then heated under vacuum at 280°C for 2 hours. Thus, a clean-functional transport member (C1) comprising a 9.0 μm thick clean layer (C1) was obtained. The clean-functional transport member (C1) comprises a clean sheet (C1) formed from the clean layer (C1) and a silicon wafer used as the transport member.
[0159] The results are shown in Table 1.
[0160] [Comparative Example 2]
[0161] (Preparation of modified polybenzoxazole varnish)
[0162] 43.8 g of 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol), 64.4 g of H2N-CH(CH3)-CH2-(O-CH(CH3)-CH2)2-(O-CH2CH2CH2CH2)9-(O-CH2-CH(CH3))3-NH2 (trade name: “ELASTAMINE RT-1000”, manufactured by Huntsman Corporation, molecular weight: 1,000), 47.0 g of pyridine, and 600 g of N-methyl-2-pyrrolidone were placed in a detachable flask equipped with a stirrer, and the mixture was stirred at room temperature until 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol) and ELASTAMINE RT-1000 were completely dissolved. Then, 32.6 g of trimethylchlorosilane was added dropwise to the flask over 10 minutes, and the mixture was stirred at room temperature for 60 minutes. Then, 54.3 g of 4,4′-bis(chlorocarbonyl)diphenyl ether was slowly added to the flask over 10 minutes, and the mixture was stirred at room temperature for 2 hours.
[0163] The resulting synthetic solution was added dropwise to 10 L of ion-exchanged water, and the resulting precipitate was dried at 120 °C for 4 hours. Four times the volume of N-methyl-2-pyrrolidone was added to the dried precipitate to redissolve it. Thus, a varnish of modified polybenzoxazole (C2) was obtained. The viscosity of the obtained varnish of modified polybenzoxazole (C2) was 880 mPa·s.
[0164] (Including the manufacture and evaluation of conveyor components with cleaning functions in the cleaning layer)
[0165] The modified polybenzoxazole (C2) varnish was applied to the mirror surface of a 12-inch silicon wafer using a spin coater (manufactured by Tokyo Electron Limited, ACT-12, 800 rpm, spin time = 30 seconds) and left to stand for 300 seconds. The varnish was then heated at 100°C for 10 minutes to remove N-methyl-2-pyrrolidone. The residue was then heated under vacuum at 280°C for 2 hours. Thus, a clean-functional transport member (C2) comprising a 7.2 μm thick clean layer (C2) was obtained. The clean-functional transport member (C2) comprises a clean sheet (C2) formed from the clean layer (C2) and a silicon wafer used as the transport member.
[0166] The results are shown in Table 1.
[0167] [Comparative Example 3]
[0168] (Preparation of modified polybenzoxazole varnish)
[0169] 43.8 g of 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol), 64.4 g of H2N-CH(CH3)-CH2-(O-CH(CH3)-CH2)2-(O-CH2CH2CH2CH2)9-(O-CH2-CH(CH3))3-NH2 (trade name: “ELASTAMINE RT-1000”, manufactured by Huntsman Corporation, molecular weight: 1,000), 47.0 g of pyridine, and 600 g of N-methyl-2-pyrrolidone were placed in a detachable flask equipped with a stirrer, and the mixture was stirred at room temperature until 4,4′-(hexafluoroisopropylidene)bis(2-aminophenol) and ELASTAMINE RT-1000 were completely dissolved. Then, 32.6 g of trimethylchlorosilane was added dropwise to the flask over 10 minutes, and the mixture was stirred at room temperature for 60 minutes. Then, 54.3 g of 4,4′-bis(chlorocarbonyl)diphenyl ether was slowly added to the flask over 10 minutes, and the mixture was stirred at room temperature for 2 hours.
[0170] The resulting synthetic solution was added dropwise to 10 L of ion-exchanged water, and the resulting precipitate was dried at 120 °C for 4 hours. Four times the volume of N-methyl-2-pyrrolidone was added to the dried precipitate to redissolve it. Thus, a varnish of modified polybenzoxazole (C3) was obtained. The viscosity of the obtained varnish of modified polybenzoxazole (C3) was 880 mPa·s.
[0171] (Including the manufacture and evaluation of conveyor components with cleaning functions in the cleaning layer)
[0172] The modified polybenzoxazole (C3) varnish was applied to the mirror surface of a 12-inch silicon wafer using a spin coater (manufactured by Tokyo Electron Limited, ACT-12, 1,000 rpm, spin time = 30 seconds) and left to stand for 999 seconds. The varnish was then heated at 100°C for 10 minutes to remove N-methyl-2-pyrrolidone. The residue was then heated under vacuum at 280°C for 2 hours. Thus, a clean-functional transport member (C3) comprising a 6.9 μm thick clean layer (C3) was obtained. The clean-functional transport member (C3) comprises a clean sheet (C3) formed from the clean layer (C3) and a silicon wafer used as the transport member.
[0173] The results are shown in Table 1.
[0174]
[0175] The cleaning sheet and the conveying member with cleaning function according to at least one embodiment of the present invention are each suitable for cleaning various substrate processing devices, such as production devices and inspection devices.
[0176] According to at least one embodiment of the present invention, a cleaning sheet comprising a cleaning layer can be provided, which is applicable to a transport member conveyed within a substrate processing apparatus. This cleaning sheet effectively suppresses adsorption errors when the cleaning layer is adsorbed onto an adsorption stage or the like. Alternatively, a transport member with a cleaning function can be provided, comprising such a cleaning sheet and a transport member.
Claims
1. A cleaning sheet comprising a cleaning layer, in, When the direction from the end of the surface toward its center when viewed from the normal direction relative to the surface of the cleaning layer is defined as the center direction; and When the area occupied by a width of 10 mm from the end toward the center in the surface is defined as the end region, The relationship between the maximum thickness L of the cleaning layer in the normal direction in the end region and the average thickness T of the cleaning layer in the normal direction in the regions other than the end region is 0 < L ≤ 5 μm. The portion of the cleaning layer having a thickness greater than the average thickness T by more than 1 μm has a width "d" of less than 4,000 μm in the central direction.
2. The cleaning sheet according to claim 1, wherein the cleaning layer comprises at least one selected from the group consisting of: polyimide resins; and polybenzoxazole resins.
3. The cleaning sheet according to claim 1, wherein the thickness of the cleaning layer is 1 μm to 100 μm.
4. The cleaning sheet according to claim 1, further comprising a pressure-sensitive adhesive layer.
5. The cleaning sheet according to claim 1, further comprising a support.
6. A conveying component with a cleaning function, comprising: The cleaning sheet according to claim 1; and Conveying components.
Citation Information
Patent Citations
Cleaning sheet, conveying member with cleaning function, and cleaning method of substrate treatment apparatus
JP2007307521A
Cleaning sheet, conveying member with cleaning function, method of cleaning base treatment device and base treatment device
JP2010259970A
Cleaning sheet and carrying member with a cleaning function
CN111500185A
Manufacturing method of carrying member with cleaning function
JP2006216870A